2019
DOI: 10.1371/journal.pone.0217592
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding climate change from a global analysis of city analogues

Abstract: Combating climate change requires unified action across all sectors of society. However, this collective action is precluded by the ‘consensus gap’ between scientific knowledge and public opinion. Here, we test the extent to which the iconic cities around the world are likely to shift in response to climate change. By analyzing city pairs for 520 major cities of the world, we test if their climate in 2050 will resemble more closely to their own current climate conditions or to the current conditions of other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 28 publications
1
76
0
1
Order By: Relevance
“…The explicit inclusion of ecohydrology and subsurface hydrology in urban canopy modelling leads to an improved simulation during dry-down periods, as shown in Singapore. This is of particular interest as dry periods may increase in many cities in the future (Bastin et al, 2019) and allow UT&C to analyse the response of urban vegetation under different climate scenarios. Furthermore, UT&C is potentially more accurate in predicting relative humidity at pedestrian level given its more comprehensive inclusion of soil and vegetation processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The explicit inclusion of ecohydrology and subsurface hydrology in urban canopy modelling leads to an improved simulation during dry-down periods, as shown in Singapore. This is of particular interest as dry periods may increase in many cities in the future (Bastin et al, 2019) and allow UT&C to analyse the response of urban vegetation under different climate scenarios. Furthermore, UT&C is potentially more accurate in predicting relative humidity at pedestrian level given its more comprehensive inclusion of soil and vegetation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Nature-based solutions, such as the increase of urban vegetation, are often encouraged to mitigate UHI and decrease surface runoff as part of a sustainable urban development (Lim and Lu, 2016;Roth, 2007;Bowler et al, 2010;Pataki et al, 2011;Li et al, 2014;Gillner et al, 2015). For instance, urban trees provide shade for pedestrians and evaporative cooling (Bowler et al, 2010;Konarska et al, 2016), while an increase in ground vegetation can further provide storm water retention (Berland et al, 2017). In addition to urban climate and water regulation, urban vegetation also provides other ecosystem services, for example, carbon storage (Nowak and Crane, 2002), enhanced biodiversity (Grimm et al, 2008), and aesthetic, cultural, and health benefits (Salmond et al, 2016;Ng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by the consultancy firm Verisk Mapelcroft, combining United Nations projections on the rates of annual population growth in over 1800 cities with subnational data on climate change vulnerability, showed that of the 100 fastest growing cities by population, 84 are rated extreme risk, with a further 14 in the high risk category over the next 30 years [51]. Another recently reviewed study covering 520 major cities in the world, concludes that even in an optimistic climate scenario (the RCP 4.5 scenario) all the cities are likely to experience major climatic shifts by 2050 [52]. More specific, the study concludes that cities from the northern hemisphere in general are likely to experience a temperature increase equivalent to moving 1000 km south, whereas cities from the tropics are expected to shift to drier conditions.…”
Section: Sustainable Urban Tourism: Part Of the Sustainable Developmementioning
confidence: 99%
“…Current research shows clearly, that urban areas are more vulnerable to climate change than rural areas [2][3][4]. A recent publication from Bastin et al [5] illustrates the impacts of climate change on large cities using city analogies. For 77% of all global large cities a climatic analogy could be found, comparing their respective climate in 2050 to that of large cities today.…”
Section: Introductionmentioning
confidence: 99%